Spontaneous uvula hematoma: an unusual case - Baran, Hacer; Gokdogan, Ozan (The European Research Journal, 2015)
Hematomas in upper aerodigestive tract are not rare especially in patients with cardiologic conditions.Without comorbidities, it can also be seen after trauma cases. Sponatenous hematoma is a rare clinical condition that needs detailed evaluation especially for hematologic and immunologic disorders. We describe a case with spontaneus uvula hematoma. We describe a case with spontaneus uvula hematoma, without a history of trauma and anticoagulant therapy. We also discussed the management strategies. This patient with those findings, appears to be the firts case that was published in the English-language literature.